Boxing changes chemokine production by PBMC - Khanferyan, R.; Riger, N.; Korosteleva, M.; Dubuske, L. (The Journal of Allergy and Clinical Immunology, 2021)
Rationale: Boxing is a sport requiring significant endurance training. Such training may influence production of both cytokines and chemokines leading to persistent inflammation. This investigation uses peripheral blood mononuclear cells (PBMC) to assess production of chemokines in boxers during training. Methods: Professional boxers in intensive training period and healthy controls were assessed for chemokine production by PBMC after 72 hours culture by assaying the culture supernatants using "ProcartaPlexTMH. Cyto- / Chemokine/Growth Factor Panel 1"(eBioscience, Austria) and Luminex 200 equipment (Luminex Corporation, USA). Results: Boxers were shown to have greater amounts of select chemokines in the PBMC supernatants including MIP-1 beta, GRO-alpha, RANTES, SDF-1-alpha and IL-8 (P<0.05). Healthy controls however had greater supernatants levels of MCP-1, Eotaxin, and MIP-1 alpha. PBMC of the control group stimulated by Con-A had supernatants with lower amounts of and SDF-1-alpha GRO-alpha, and IL-8, and increased MIP-1 beta whereas boxers showed decreases in RANTES but significant (p<0.05) increases in SDF-1alpha, Eotaxin, IL-8, GRO-alpha, IL-8 MCP-1, MIP-1 alpha, and MIP-1 beta consistent with an impact of endurance training on chemokine production. Conclusions: Chemokine production assessed by PBMC supernatant assays may be a useful tool for assessing immune changes developing during endurance training of boxers.